UPAYA PACIFIC ISLAND FORUM DALAM MENGATASI MASALAH PERUBAHAN IKLIM DI KAWASAN KEPULAUAN PASIFIK - Erina Aulia (Jurusan Ilmu Pemerintahan Universitas Palanfka Raya, 2023)
Pacific islands are at risk due to climate change because they are in a state of high risk. Because their islands are smaller and surrounded by vast oceans. The occurrence of climate change in the Pacific islands has affected many, including the island of Tuvalu, which has been forced to immigrate because their uninhabitable homes due to storms and extreme weather events have damaged ecosystems and destroyed the livelihoods of its inhabitants. Climate change is then an environmental issue that is currently a topic that continues to be discussed by international relations, then the Pacific Island Forum (PIF) seeks to address climate change that occurs in the Pacific islands and create a Framework for the Resilient Development of the Pacific (FRDP) then, PIF also helps empower communities through training and financial assistance. PIF also cooperates with various countries, one of which is through its meeting with Japan and the United States. PIF endorsed the Kainaki II Declaration for Urgent Climate Change Action and agreed to formulate a 2050 Strategy for the Blue Pacific Continent.